(untitled) (Latakia University Journal -Basic Sciences Series, 2014)
لقد أوجدنا في هذه البحث مجموعة من الحلول التامة لمعادلة Fitzhugh-Nagumo المعمّمة ذات الأمثال الثابتة، باستخدام طريقة التكامل الأول، ووجدنا من خلال عملية إيجاد هذه الحلول أنّ هذه الطريقة فعّالة مع هذا النوع من المعادلات التفاضلية غير الخطية. In this work, we have been obtained exact solutions for generalized Fitzhug-Nagumo equation with constant coefficients, by using the first integral method, and we have shown that this method is an efficient method to obtain exact solutions to this kind of nonlinear partial differential equations.